Lactic Acid Level as A Predictor of Severity in Patients with Acute Appendicitis (Majalah Kedokteran Bandung, 2024)
Perforated appendicitis is the leading cause of morbidity and mortality of all appendicitis cases in adults and children, with delayed preoperative diagnosis as the main reason. In previous studies, diagnostic modalities such as radiological examination and the current scoring system have been demonstrated as unable to predict the onset of perforated appendicitis. Serological biomarkers of lactic acid are associated with intestinal obstruction and ischemia. The serological value of lactic acid in identifying perforated appendicitis compared to acute one was shown to increase significantly by 0.25 mmol/L (p
Keywords: Correlation; lactic acid; perforated appendicitis